2005
DOI: 10.1300/j069v24n02_08
|View full text |Cite
|
Sign up to set email alerts
|

Methadone Maintenance and Male Sexual Dysfunction

Abstract: The rate of global sexual dysfunction in methadonetreated men is similar to general population studies and should be evaluated using general population guidelines. Orgasm dysfunction is a special case and may respond to methadone dose reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
75
6
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(95 citation statements)
references
References 44 publications
13
75
6
1
Order By: Relevance
“…Hallinan (2008) also reported that depression was found to be associated with global sexual dysfunction in groups of patient on MMT or buprenorphine. Our study results revealed that the presence of depressive symptoms was not associated with respondents with erectile dysfunction; this is consistent with the findings of Niclaas et al (2005) and Brown et al (2005). Though not significant, it is worth noting that a higher percentage of respondents with depressive symptoms had erectile dysfunction compared to those without.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Hallinan (2008) also reported that depression was found to be associated with global sexual dysfunction in groups of patient on MMT or buprenorphine. Our study results revealed that the presence of depressive symptoms was not associated with respondents with erectile dysfunction; this is consistent with the findings of Niclaas et al (2005) and Brown et al (2005). Though not significant, it is worth noting that a higher percentage of respondents with depressive symptoms had erectile dysfunction compared to those without.…”
Section: Discussionsupporting
confidence: 91%
“…Spring et al (1992) suggested that methadone patients presenting with sexual dysfunction should receive psychiatric evaluation after he found a significant association between lower Global Sexual Satisfaction Index scores with low Hamilton Rating Scale for Depression scores. Hallinan et al (2008) and Brown et al (2005) used the Beck Depression Inventory (BDI) to measure the presence of depression in methadone patients and reported significant association with erectile dysfunction. Contrary to Bliesener et al (2005), who used a two-question self-rating scale for sexual function, depression as measured by BDI was not associated with erectile dysfunction in neither methadone nor buprenorphine groups.…”
Section: Introductionmentioning
confidence: 99%
“…Une autre étude effectuée auprès de 92 hommes sous métha-done démontrait une fréquence moindre de dysfonction sexuelle de l'ordre de 14 % (Brown, Balousez, Mundt, & Fleming, 2005), ce qui diffère peu de la fréquence observée dans la population générale. La dysfonction augmentait avec l'âge et la dose de méthadone.…”
Section: Effets Indésirables Plus Spécifiquement éTudiésunclassified
“…Plasma testosterone levels have been revealed to be lower in opiate addicts, as compared with controls (26). Patients on lower doses of heroin and methadone have been found to have higher testosterone levels (27).…”
Section: Introductionmentioning
confidence: 99%